It's all about the children: a participant-driven photo-elicitation study of Mexican-origin mothers' food choices - Sharkey Joseph R; Johnson Cassandra M; Dean Wesley R (BMC, 2011)
Abstract Background There is a desperate need to address diet-related chronic diseases in Mexican-origin women, particularly for those in border region colonias (Mexican settlements) and other new destination communities in rural and non-rural areas of the U.S. Understanding the food choices of mothers, who lead food and health activities in their families, provides one way to improve health outcomes in Mexican-origin women and their children. This study used a visual method, participant-driven photo-elicitation, and grounded theory in a contextual study of food choices from the perspectives of Mexican-origin mothers. Methods Teams of trained promotoras (female community health workers from the area) collected all data in Spanish. Ten Mexican-origin mothers living in colonias in Hidalgo County, TX completed a creative photography assignment and an in-depth interview using their photographs as visual prompts and examples. English transcripts were coded inductively by hand, and initial observations emphasized the salience of mothers' food practices in their routine care-giving. This was explored further by coding transcripts in the qualitative data analysis software Atlas.ti. Results An inductive conceptual framework was created to provide context for understanding mothers' daily practices and their food practices in particular. Three themes emerged from the data: 1) a mother's primary orientation was toward her children; 2) leveraging resources to provide the best for her children; and 3) a mother's daily food practices kept her children happy, healthy, and well-fed. Results offer insight into the intricate meanings embedded in Mexican-origin mothers' routine food choices. Conclusions This paper provides a new perspective for understanding food choice through the eyes of mothers living in the colonias of South Texas -- one that emphasizes the importance of children in their routine food practices and the resilience of the mothers themselves. Additional research is needed to better understand mothers' perspectives and food practices with larger samples of women and among other socioeconomic groups.